Ocorrência de agrotóxicos em águas rurais e bioacumulados em biofilmes epilíticos do Rio Grande do Sul - Lima, José Augusto Monteiro de Castro (2017)
In Brazil, agricultural activities have a high potential for contamination of water resources, especially by pesticides use. This potential is highest in river basins where agriculture is developed out of agricultural aptitude and without adequate land use planning. However, the severity of this context has been disregarded for two reasons: i. by the understanding that no-tillage system (SPD), as adopted in Rio Grande do Sul, is effective in controlling pollution; and ii. due to technical limitations and/or absence of hydrographic basin monitoring systems. Recently, the development of POCIS (Polar Organic Chemical Integrative Sampler) and use of epilithic biofilms has sought to improve monitoring systems. However, neither POCIS was tested in Brazilian tropical conditions, nor biofilms were used in agrochemical monitoring. In this context, this doctorate thesis aims to monitor the presence of active pesticides in river waters of river basin in state of Rio Grande do Sul (RS). Monitoring was performed in the Guaporé River Basin because it was representative of use conditions and management of the physiographic region of Plateau–RS. Same was done by three sampling methods: active sampling, passive sampling with POCIS and passive sampling with biofilms, at 08 points under the influence of SPD, 09 points in conventional planting areas and 1 point in forest area. In the three sampling methodologies the occurrence and concentration of pesticides, associated or not with the systems of use and management practiced in the basin, were verified. In active sampling, 11 active ingredients were detected from the 79 analysis. This methodology was unable to detect the active ingradients of high polarity (2,4-D) and those of lower polarity epoxiconazole and tebuconazole and presented no statistical difference between management systems. The adoption of POCIS in less frequent frequency of use and application, allowed the detection of compounds that had not been detected in the active sampling, besides increasing the frequency of detection of each active ingradient. The management systems were differentiated by the higher concentration of fungicides, epoxiconazole and tebuconazole, used in soybean crops in SPD. Sampling using epilite biofilms detected a greater number of active ingradients in the Guaporé River Basin, and the frequency of detection of each pesticide was higher than the other sampling methodologies. Regarding land use and management systems, biofilms confirmed that the main difference between them is related to the higher concentration of fungicides in areas under SPD. In three monitoring systems it was verified that all the points sampled, regardless of the system of use and management, are contaminated by agrochemicals, even the forest area. In addition, the highest concentrations of agrochemicals in the Guaporé river system are located on its main river and follow the flow direction of water. Epilithic biofilms were more promising to detect contamination than the active and POCIS sampling techniques, since they captured active pesticides indistinctly from their polarizations, even in the period of less application.